PERAN LITERASI KEUANGAN DALAM MENINGKATKAN PENGELOLAAN KEUANGAN UMKM DI KELURAHAN KEBONSARI KOTA SURABAYA - Dzakiyah, Annisa Aliyyatud; Munari, Munari (Jurnal Riset Akuntansi & Keuangan, 2024)
This research aims to dig knowledge of financial literacy relations in improving the financial management of MSME perpetrators in Kelurahan Kebonsari Kota Surabaya. This research uses a type of qualitative descriptive research. The reason why he did this research is that there are still more than 15 MSME Kelurahan Kebonsari who have not had literacy knowledge in the financial management of enterprises well. The author uses purposive sampling techniques taking into account specific criteria such as who is considered capable of meeting the research criteria. In sampling, the author conducted a selection against three MSME perpetrators. The three main informants in this study are MSME persons who have a turnover of over 15 million per month, have been operating for more than 5 years, and one of the informants is the head of MSME in Kelurahan Kebonsari. The results of the research show that the three informants sufficiently understand financial literacy, the financial management of the informants is done manually and through applications. On the other hand, the financial literacy of other MSME perpetrators in Kelurahan Kebonsari is still low. Increased financial literacy is essential for MSME perpetrators in Kelurahan Kebonsari to improve their financial management